Association of Sp1 Tandem Repeat Polymorphism of ALOX5 with Coronary Artery Disease in Indian Subjects - Todur, Seema P. (Clin Transl Sci, 2012)
Lipoxygenases have been implicated in the pathogenesis of coronary artery disease (CAD) for its potent proinflammatory role. The Sp1 addition/deletion polymorphism in promoter region of the 5‐lipoxygenase gene (ALOX5) has been associated with increased risk of carotid atherosclerosis and myocardial infarction. To determine the role of this polymorphism in our population we performed a case–control‐genetic association study on 117 healthy controls and 119 angiographically verified CAD patients. Biochemical analysis was performed using standard automated assays. High‐density lipoprotein cholesterol (HDL‐C) and LDL‐C subfraction levels were estimated using precipitation methods. Genotyping of polymorphism in the ALOX5 (Sp1 variants) was done using PCR‐based heteroduplex analysis and automated sequencing. The Sp1 promoter repeat variants were found to be associated with CAD (p < 0.0001, OR = 4.47, 95% confidence interval = 2.58–7.74). Furthermore, the 5/5 genotype of the ALOX5 polymorphism in the healthy subjects was found to be associated with elevated HDL‐C (p= 0.004), HDL(3)‐C (p= 0.04), apo A1 (p= 0.011) and sdLDL (p= 0.001). We conclude that this polymorphism influences LDL and HDL subfraction levels and is a risk factor for CAD in our population. Clin Trans Sci 2012; Volume 5: 408–411